2017
DOI: 10.4103/0972-2327.199904
|View full text |Cite
|
Sign up to set email alerts
|

Etiological profile of noncompressive myelopathies in a tertiary care hospital of Northeast India

Abstract: Background:The discovery of antibodies against aquaporin-4 and evolving concepts of noncompressive myelopathies in the 21st century have made a major impact on the etiological profile of these diseases, with few cases turning out to be idiopathic.Objective:To find causes of noncompressive myelopathy in a tertiary care hospital of Northeast India.Materials and Methods:An observational study was carried out in the Neurology Department of Gauhati Medical College, Guwahati, from September 2013 to February 2016. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Another study conducted in North East India which included 151 patients of noncompressive myelopathy with 35 years as their median age and a sex ratio of 1.4:1 showing a male predominance. 14 In the present series, 28 years was our median age with a sex ratio of 1:2 showing a female predominance. Similar age and gender profile were observed in other previous studies.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Another study conducted in North East India which included 151 patients of noncompressive myelopathy with 35 years as their median age and a sex ratio of 1.4:1 showing a male predominance. 14 In the present series, 28 years was our median age with a sex ratio of 1:2 showing a female predominance. Similar age and gender profile were observed in other previous studies.…”
Section: Discussionmentioning
confidence: 43%
“…Another study concluded acute myelitis in 66.3% and chronic myelitis in 33.6% among their group study of 151 patients of noncompressive myelopathy. 14 In the present series, paraparesis (84%) was the most common clinical manifestation, with acute presentation in 40%, subacute in 31%, and chronic in 28% of patients. The most common location among the diagnosed case was cervico-dorsal cord (12 patients), cervical (5 patients), dorsal (4 patients), and dorsolumbar in 3, with the entire cord involvement in 2 patients.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Kayal et al [95] performed a study aiming to establish the cause of several noncompressive myelopathies in a tertiary care hospital in India. Thus, 55 patients with non-compressive myelopathies were diagnosed, after the MRI of their spine, with chronic myelopathy (CM).…”
Section: Localized In Vivo Nuclear Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…The causes of vitamin B 12 deficiency were determined to be combinations of a strict vegetarian diet, malnutrition, alcohol consumption, and phenytoin therapy. Although MRS was mentioned as a performed analysis, no details have been given and only MRI details and images have been presented [95].…”
Section: Localized In Vivo Nuclear Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%